Spatial Differences in Cellular and Molecular Responses as a Function of the Material Used in Conduit‐Mediated Repair and Autograft Treatment of Peripheral Nerve Injuries. (31st August 2017) - Daly, William T.; Niemier, Ryan; Dillon, Simon T.; Wang, Huan; Mirsky, Rhona; Jessen, Kristjan; Windebank, Anthony; Pandit, Abhay
Abstract: The treatment of peripheral nerve injuries remains a major problem worldwide despite the availability of a number of Food and Drug Administration (FDA) approved devices which fail to match the efficacy of autografts. Different strategies are used to improve regeneration and functional recovery using biomaterial nerve conduits. However, there is little investigation of the transcriptomic and proteomic changes which occur as a result of these interventions, particularly regarding transection injuries. This study explores differences between autograft‐mediated repair and conduit‐material‐mediated repair of peripheral nerve injuries to understand fundamental differences in their repair mechanisms at the proteomics level at the proximal, middle, and distal components in the early stages of repair. Pathway analysis demonstrates that each material selectively activates different regenerative pathways and alters different biological functions spatially throughout the biomaterial conduits. The analysis highlights some of the deficiencies in conduit‐mediated repair in comparison to autograft (e.g., recycling of myelin and cholesterol, reduction in reactive oxygen species, and higher expression of regenerative proteins). These findings thus suggest that by supplementing the expression of these proteins on the biomaterial of choice, this study can potentially attain regeneration equivalent to autograft. This approach paves the way for incorporating future biomaterial‐specific functionalities in nerve guidance conduits. Abstract : The proteomic changes that occur spatially throughout a natural or synthetic nerve guidance conduit or within an autograft during the treatment of peripheral nerve injuries are investigated in this study. Using pathway analysis tools, this study explores how different materials in conduit‐mediated nerve repair, and how autografts, activate different biological functions during the early stages of regeneration.